Fulminant necrotizing fasciitis following the use of herbal concoction: a case report - Adigun, Ismaila A (BioMed Central, 2010)
INTRODUCTION: Necrotizing fasciitis is a rare and life-threatening rapidly progressive soft tissue infection. A fulminant case could involve muscle and bone. Necrotizing fasciitis after corticosteroid therapy and intramuscular injection of non-steroidal anti-inflammatory drugs has been reported. We present a case of fulminant necrotizing fasciitis occurring in a patient who used a herbal concoction to treat a chronic leg ulcer. CASE PRESENTATION: A 20-year-old Ibo woman from Nigeria presented with a three-year history of recurrent chronic ulcer of the right leg. She started applying a herbal concoction to dress the wound two weeks prior to presentation. This resulted in rapidly progressive soft tissue necrosis that spread from the soft tissue to the bone, despite aggressive emergency debridement. As a result she underwent above-knee amputation. CONCLUSION: The herbal concoction used is toxic, and can initiate and exacerbate necrotizing fasciitis. Its use for wound dressing should be discouraged.